2011
DOI: 10.1002/hbm.21446
|View full text |Cite
|
Sign up to set email alerts
|

Common structural correlates of trait impulsiveness and perceptual reasoning in adolescence

Abstract: The neural correlate of trait impulsiveness in the OFC matches an area where brain function has previously been related to inhibitory control. Additionally, orbitofrontal GM volume was associated with scores for perceptual reasoning. The data show for the first time structural correlates of both cognitive functioning and impulsiveness in healthy adolescent subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 98 publications
4
34
0
2
Order By: Relevance
“…We found a negative correlation between impulsivity and SA of the insula and STC in cocaine users but a positive correlation in controls, which is in line with previous studies showing similar correlations with CV of these regions (Churchwell and Yurgelun-Todd, 2013;Ersche et al, 2011;Moreno-López et al, 2012;Schilling et al, 2012). In addition, a positive correlation was shown between CT of the ACC in cocaine users, but a negative correlation in controls, similar to what has been found for CV of other prefrontal regions (Crunelle et al, 2014;Matsuo et al, 2009;Moreno-López et al, 2012;Schilling et al, 2012Schilling et al, , 2013. Our study expands on previous studies by showing that the relation between cortical morphometry and impulsivity is different for SA and CT.…”
Section: The Relation Between Impulsivity and Cortical Morphometrysupporting
confidence: 91%
“…We found a negative correlation between impulsivity and SA of the insula and STC in cocaine users but a positive correlation in controls, which is in line with previous studies showing similar correlations with CV of these regions (Churchwell and Yurgelun-Todd, 2013;Ersche et al, 2011;Moreno-López et al, 2012;Schilling et al, 2012). In addition, a positive correlation was shown between CT of the ACC in cocaine users, but a negative correlation in controls, similar to what has been found for CV of other prefrontal regions (Crunelle et al, 2014;Matsuo et al, 2009;Moreno-López et al, 2012;Schilling et al, 2012Schilling et al, , 2013. Our study expands on previous studies by showing that the relation between cortical morphometry and impulsivity is different for SA and CT.…”
Section: The Relation Between Impulsivity and Cortical Morphometrysupporting
confidence: 91%
“…Asahi et al (2004) have shown that activation in the right dorsolateral prefrontal cortex recruited by response inhibition in the NoGo task is inversely correlated with individual impulsivity. Greater impulsiveness has also been correlated with lesser gray matter volume in frontal regions associated with inhibition and flexible control of behavior, including orbitofrontal cortex, middle frontal gyrus, and superior frontal gyrus (Schilling et al, 2011(Schilling et al, , 2012. The current study establishes the utility of our emotional Go/ NoGo task for investigating modulation of impulse control by task- Fig.…”
Section: High Risk Behaviorsupporting
confidence: 66%
“…For most of the population, the occurrence of ASB peaks in adolescence when situational ASB is common, even normative, then declines as the individual enters early adulthood (10). Like ASB, impulsivity is also a multifactorial construct that likely depends on multiple brain structures (16,62,63). Separate investigations would be required to examine the potential contribution of these other types of impulsivity to ASB.…”
Section: Discussionmentioning
confidence: 99%